Arthroplasty of the knee six months after surgery, the return to fitness - Grażyna Maksimczyk-Wrona; Maciej Ornat; Wojciech Tokarski; Eleonora Anna Mess (Kazimierz Wielki University, 2019)
Degenerative joint disease (osteoarthritis) is a chronic disorder of the musculoskeletal system, which significantly reduces the efficiency of movement and daily functioning difficult. The last twenty years is a huge progress in the diagnosis and treatment of degenerative changes in the knee joint. Currently knee replacement is a fundamental activity in patients with large destructive changes in the joint. Studies carried out in the clinic Trauma Surgery at the University Teaching Hospital in Wroclaw, ul. Borowski group of 105 patients. In this study, we observed that there was an improvement of quality of life after surgery, knee replacement, especially in people at a younger age. The pain persisted completely, but reduced in intensity. Women often suffer from arthritis and achieve better results on the knee. It was also shown that younger people better cope with the activities of daily living and have less pain from the knee joints. This suggests that a return to efficiency and improve the functioning of younger people should be achieved in a shorter time than adults, whose efficiency is further limited by the patient's age.